The Communication Effectiveness of Scientist-Stakeholder Partnerships Addressing Agriculture and Natural Resources Issues: An Analysis of the Media Attention and Media Framing of the Florida Water and Climate Alliance - Shuyang Qu; Tracy Irani (Journal of Applied Communications, 2018)
Scientist-stakeholder partnerships are formed by scientists from academic institutions and industry representatives in an effort to address contingent science issues such as climate change, inform the public and influence public policies. Such organizations often lack expertise in communicating to the public and conducting outreach which are crucial components to building a good reputation. This study selected Florida Water and Climate Alliance [FWCA] as an example of such an organization, exploring its media attention and media framing to assess the visibility and reputation of [FWCA]. Results showed very limited media attention had been devoted to [FWCA]. The framing analysis results indicated that the coverage of [FWCA] is mostly introductory and descriptive information from public institutions, collaborators and funding agencies. These results demonstrate the need for such organizations to increase media visibility and build their reputations through strategic communication. Scientist-stakeholder partnership organizations like FWCA could gain from strategic collaborations with agricultural communications professionals and academic researchers. To better assist in building the reputation for these organizations, recommendations include developing strategic communication plans and conducting research about stakeholders’ and collaborators’ perceptions of an organization’s reputation.
Keywords: Scientist-stakeholder partnerships; media attention; visibility; framing; reputation